The role of feedback in building teaching presence and student self-regulation in online learning - Laura Morrison; Michele Jacobsen (Social Sciences and Humanities Open, 2023)
In this research we studied usable strategies to promote student engagement and learning in the online classroom specifically connected to the development of teaching presence and student self-regulation. A design-based research approach (Barab & Squire, 2004) with multiple methods of data collection were used in the study's design, which was informed by the Garrison et al.’s Community of Inquiry framework and Zimmerman's cycle of self-regulatory phases. Qualitative sources of data included coursework and semi-structured interviews with three student participants, accompanied by text-based planning and debrief notes, and a semi-structured interview with one instructor. The study context was an online course connected to a Bachelor of Education program at a university in Ontario, Canada. Findings indicate students experienced teaching presence directly in the timely, strengths-based and personal feedback they received. Regular feedback helped students know their work was being seen and that they were “on the right track”. Strengths-based and personal feedback aided student motivation and self-regulation, which emerged as important for ongoing engagement and learning online. Recommendations that emerged from this study are of interest internationally to designers of online learning courses, online instructors and researchers in online learning.